Effect of single and combined ocean motions on a small OFNP under SBO accidents. (15th September 2020) - Yan, Qiqi; Luo, Simin; Zhang, Yapei; Chen, Ronghua; Su, G.H.
Highlights: An ocean condition available analysis code based on RELAP5 MOD3.3 is developed. Effects of single heaving and single rolling motion on OFNP under SBO were discussed. Effects of combined motion of heaving and rolling on OFNP under SBO were discussed. Abstract: In view of the safety characteristics of the offshore floating nuclear plant (OFNP), an ocean condition available analysis code based on RELAP5 MOD3.3 is developed and the influences of single heaving, single rolling and combined motion of heaving and rolling on a OFNP were analyzed under station blackout accident (SBO). The results indicate that heaving motion accelerates the drop in the reactor pressure. The flow fluctuation caused by heaving motion promoted the derivation of residual heat after SBO; Rolling motion accelerates the declination of the reactor pressures and the coolant temperature after SBO, and also causes a large flow oscillation in pipes. The results also shows that the combined motion is more severe than these two single conditions. The parameters variation under the combined motion is more similar to that under its rolling condition. The residual heat can be removed effectively under all these conditions and the security will not be threatened.